Highly sensitive detection of the onset of solid-state phase transition in an endocrine-disrupting estrogen-like chemical using terahertz radiation - Quema, Alex (Animo Repository, 2005)
Using terahertz transmission spectroscopy, solid-state phase transition onset in an estrogen-like chemical is detected. This is indicated by the observation of two broad absorption peaks and sudden upsurge of terahertz-radiation power at 210 K. © 2005 Optical Society of America.